Monitoring the physical processes driving the mass loss of Tapado Glacier, Dry Andes of Chile - Ayala, Alvaro; Robson, Benjamin; Navarro, Gonzalo; MacDonell, Shelley; Kinnard, Christophe; Vivero, Sebastian; Thomas, Daniel; Moreno, Felipe; Yanez, Eduardo; Schaffer, Nicole; Segovia, Alexis; Petlicki, Michal; et al. (My University, 2025)
We summarise 15 years of field and remote monitoring of Tapado Glacier in north-central Chile (30 degrees S). Observations include meteorological records, direct mass balance measurements, uncrewed aerial vehicle surveys and tri-stereo satellite imagery for deriving high-resolution elevation changes. Frequent droughts and a significant warming trend of 0.29 degrees C decade-1 since 1974 have caused a decrease in glacier surface albedo and an accelerated loss of glacier area and mass, particularly since the onset of the Chilean Megadrought in 2010, associated here with a 43% winter precipitation deficit. Geodetic estimates indicate increasingly more negative mass balance, varying from slightly negative before 2000 to -0.18 +/- 0.35 m w.e. a-1 in 2000-12, -0.44 +/- 0.11 m w.e. a-1 in 2012-20 and -0.75 +/- 0.12 m w.e. a-1 after 2020. Glacier mass loss is associated with several morphological changes, such as increased penitente height, a larger total surface area of ice cliffs and supraglacial ponds over the debris-covered section and more frequent falls of snow and ice from marginal ice surrounding a steep area of exposed bedrock. Tapado Glacier exemplifies how glacier mass loss is driven by various processes, requiring multiple monitoring techniques, and highlights the accelerated changes of the Andes cryosphere.
Keywords: climate change; glacier ablation phenomena; glacier mass balance; glacier monitoring